2005
DOI: 10.1080/09687860500092927
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional characterization of two bacterial members of the NAT/NCS2 family inEscherichia coli

Abstract: The coding potential of the genome of E. coli K-12 includes YgfO and YicE, two members of the evolutionarily conserved NAT/NCS2 transporter family that are highly homologous to each other (45% residue identity) and closely related to UapA of Aspergillus nidulans, a most extensively studied microbial member of this family. YgfO and yicE were cloned from the genome, over-expressed extrachromosomally and assayed for uptake of [(3)H]xanthine and other nucleobases, in E. coli K-12, under conditions of negligible ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
98
0
34

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(132 citation statements)
references
References 43 publications
0
98
0
34
Order By: Relevance
“…More than 1,000 sequence entries are known but few are functionally characterized to date. Structure-function relationships have been studied extensively in two members, the eukaryotic UapA, a high-affinity uric acid/xanthine:H ϩ symporter from the ascomycote Aspergillus nidulans (3)(4)(5)(6) and the prokaryotic YgfO, a specific, high-affinity xanthine:H ϩ symporter from Escherichia coli (7)(8)(9)(10)(11). Mutagenesis data from both lines of study have shown that key NAT determinants are strikingly similar between the two transporters, and that few residues conserved throughout the family may be invariably critical for function (10).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…More than 1,000 sequence entries are known but few are functionally characterized to date. Structure-function relationships have been studied extensively in two members, the eukaryotic UapA, a high-affinity uric acid/xanthine:H ϩ symporter from the ascomycote Aspergillus nidulans (3)(4)(5)(6) and the prokaryotic YgfO, a specific, high-affinity xanthine:H ϩ symporter from Escherichia coli (7)(8)(9)(10)(11). Mutagenesis data from both lines of study have shown that key NAT determinants are strikingly similar between the two transporters, and that few residues conserved throughout the family may be invariably critical for function (10).…”
mentioning
confidence: 99%
“…Topology model of YgfO permease. The model is based on program TMHMM, evidence that C terminus is cytoplasmic (7,15) and our unpublished evidence (see footnote 3) on the accessibility of loops to hydrophilic reagents. Irreplaceable residues of YgfO (10) are numbered and bolded.…”
mentioning
confidence: 99%
See 3 more Smart Citations